Factors associated with hypothyroidism following hemithyroidectomy: a prospective study - Chowsilpa, Sanathorn; Tananuvat, Rak (Biomedical Sciences and Clinical Medicine, 2017)
Objective To assess the incidence of post-operative hypothyroidism after hemithyroidectomy in the Thai population living in the northern region of Thailand and to analyze factors associated with hypothyroidism following hemithyroidectomy. Methods A prospective study was conducted at Chiang Mai University Hospital, Thailand, of patients who had thyroid nodules and who were scheduled for a hemithyroidectomy between September 2010 and April 2012. Patients were divided into a euthyroid group and a hypothyroid group. Demographic data, pre- and post-operative thyroid function tests, resected side, weight, and pathological diagnosis of resected thyroids were analyzed. Results Of the 50 cases, 11 patients who had documented malignancy and required total thyroidectomy and those who were lost to follow up were excluded. The study included 39 cases (7 males and 32 females) age 19 to 71 years (average 46.9±13.8 years). Left and right hemithyroidectomies were done in 25 and 14 patients, respectively. Pathology reports on the patients indicated adenomatous goiter (66.6%), follicular adenoma (20.5%), colloid cyst (5.1%), Hurthle cell adenoma (2.6%), chronic lymphocytic thyroiditis (2.6%), and nodular goiter with lymphocytic thyroiditis (2.6%). Eight cases (20.5%) had developed hypothyroidism at eight to ten weeks postoperatively. The preoperative TSH level of the hypothyroid group was normal, but signi fi cantly lower than in the euthyroid group (p =0.009). Age, pre-operative free T4 and free T3, weight, and resected side were not signifi cantly different between the two groups. More male patients than females developed post-operative hypothyroidism (42.9% VS 15.6%), although the difference was not statistically signi fi cant. Conclusions As one- fi fth of the hemithyroidectomy patients developed hypothyroidism within eight to ten weeks post-operatively, clinicians should be alert for post-operative hypothyroidism and provide prompt treatment, particularly in patients with a pre-operative high normal TSH level.